Effect of Superoxide dismutase on cryopreservation of mithun semen - Ponraj, Perumal; DE, A K; VIKRAM, R; KHATE, K; VUPRU, K; KHAN, M H; NAHAK, A K; MISHRA, P C (The Indian Journal of Animal Sciences, 2022)
The present study was designed to assess the effect of superoxide dismutase (SOD) on post thaw semen quality parameters (SQPs), kinetic profiles and seminal biochemical profiles in mithun. A total of 25 ejaculates were selected and each was split into four equal aliquots after dilution with Tris-citrate-glycerol (TCG) extender such as Group I: control, Group II, III and IV contained 50, 100 and 150 U/ml of SOD, respectively. Cryopreserved and thawed samples were analysed for their motility parameters (progressive forward and in bovine cervical mucus penetration test [BCMPT]), kinetic and velocity parameters by computer assisted sperm analyser (CASA), viability, sperm morphological and nuclear abnormalities, acrosomal, plasma membrane and nuclear integrities and sperm enzymatic leakage and biochemical (sperm cholesterol and antioxidant and oxidative stress) profiles. Study revealed a significant (p